Analisis faktor-faktor yang mempengaruhi ekspor CPO provinsi Jambi ke Malaysia - Usman Hardianto; Siti Hodijah; Rahma Nurjanah (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of the study was to determine and analyze the development of production, exchange rates, CPO prices, Malaysian GDP, and Jambi Province CPO exports to Malaysia and the effect of production, exchange rates, CPO prices, Malaysian GDP on Jambi Province CPO exports to Malaysia. The data used in this study is secondary data in the form of time series data for 2000-2017. The results show that the average development of Jambi Province CPO exports to Malaysia is 4.10% per year, Jambi Province CPO production is on average 4, 10% per year, the average exchange rate is 2.64% per year, the average CPO price is 8.63% per year, and Malaysia's GDP is 4.89% per year on average. Based on the results of multiple linear analyses, it can be concluded that CPO production, CPO prices, exchange rates, and Malaysian GDP together affect the volume of Jambi Province's CPO exports to Malaysia. While partially production and GDP have a negative and insignificant effect on Jambi Province's CPO exports to Malaysia, the exchange rate and CPO prices positively and significantly impact Jambi Province's CPO exports to Malaysia. Keywords: Production, Price, Exchange rates, Gross Domestic Product